2017
DOI: 10.1210/jc.2017-00967
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Visceral Adiposity, Subcutaneous Adiposity, and Sex Hormones in the Diabetes Prevention Program

Abstract: Among overweight adults with impaired glucose intolerance, reductions in either VAT and SAT were associated with increased total testosterone in men and higher SHBG in men and women. Weight loss may affect sex hormone profiles via reductions in visceral and subcutaneous fat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 31 publications
2
37
1
Order By: Relevance
“…Some studies have reported higher concentrations of bioavailable testosterone and thus, possibly greater androgenicity in women with increased visceral adiposity [9,11], but our results indicate that this was not the case in healthy fertile-aged women. Consistent with our data, a randomized trial of weight loss among overweight premenopausal women did not find any significant associations between changes in the amount of visceral or subcutaneous adipose tissue with changes in serum testosterone [35]. In our study, the significant differences in mRNA expression of genes between the heavier and leaner co-twins suggested that the local metabolism of androgens and estrogens in fat tissue might be altered in obesity.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have reported higher concentrations of bioavailable testosterone and thus, possibly greater androgenicity in women with increased visceral adiposity [9,11], but our results indicate that this was not the case in healthy fertile-aged women. Consistent with our data, a randomized trial of weight loss among overweight premenopausal women did not find any significant associations between changes in the amount of visceral or subcutaneous adipose tissue with changes in serum testosterone [35]. In our study, the significant differences in mRNA expression of genes between the heavier and leaner co-twins suggested that the local metabolism of androgens and estrogens in fat tissue might be altered in obesity.…”
Section: Discussionsupporting
confidence: 91%
“…Fat distribution may be an important prognostic factor for prostate cancer outcomes by serving as a marker for metabolic, hormonal, and inflammatory milieus that play a role in prostate carcinogenesis. 3,[6][7][8][9][10][11][12][13] For example, visceral fat is inversely associated with bioavailable testosterone 7,8 and adiponectin 4 and is more strongly associated with insulin resistance and proinflammatory cytokines than subcutaneous fat 6 -factors that may influence prostate cancer progression. 12,13,28,29 Further studies are needed to investigate whether the fat depots themselves exert systemic or local effects in ways that promote aggressive disease or whether they are markers for a physical activity pattern or underlying hormonal milieu that influences both fat distribution and aggressive disease.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Body fat distribution is of interest because it may be a marker for different metabolic, hormonal, and inflammatory milieus that play a role in prostate carcinogenesis. 3,[6][7][8][9][10][11][12][13] For example, visceral fat is inversely associated with bioavailable testosterone 7,8 and is more strongly associated with insulin resistance and proinflammatory cytokines than subcutaneous fat. 6 Greater intermuscular thigh fat has been associated with poorer glucose tolerance, 9 whereas subcutaneous thigh fat has been associated with more favorable metabolic factors.…”
Section: Introductionmentioning
confidence: 99%
“…There is divergent data on this subject in literature. A recent study by Kim et al on a group of Asian men with impaired glucose tolerance included in a diabetes prevention program did not show any significant relationship between visceral fat and DHEA-S [ 28 ]. DHEA-S also did not show a relationship with BMI in a study on Polish males between 20 and 49 years of age [ 29 ].…”
Section: Discussionmentioning
confidence: 99%